What am I? A non-psychological answer to a fundamental question - Erhart, Itır. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2006., 2006)
The objective of this dissertation is to provide an answer to the fundamental 'What am I?' question. The work is composed of two parts. The first part aims to reject the Psychological Account, the view which states that we are most fundamentally persons. By pointing out the problems such a view is prone to creating it aims to show that 'person' is not a substance concept, that no kind of psychological continuity, like the continuity of character traits and/or memory, is either necessary or sufficient for our persistence through time. It is argued that the emotional attitude we have towards the concept 'person' leads many philosophers like Locke, Hume, Butler, Reid, Rudder Baker, to come up with a person-centered account of identity, which in turn leads to metaphysical problems and complicates our ontology. The second part of this dissertation is an attempt to develop a version of animalism, the theory which states that we are essentially human beings, i.e., members of the biological species Homo sapiens. 'Continuous existence under the kind human being' is proposed as the criterion of diachronic identity for human beings. It is argued that this version of animalism is not faced with the problems the Psychological Account creates for itself. Finally, the theory is defended against possible criticisms the advocates the Psychological Account may come up with.
Keywords: Self (Philosophy); Animalism.; Human beings.